CURRENT STATUS OF ORAL CARE IN MECHANICALLY VENTILATED PATIENTS WITHIN A VAP PREVENTION BUNDLE AT THE ANESTHESIA AND INTENSIVE CARE CENTER (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the current status and outcomes of oral care within the ventilator-associated pneumonia prevention bundle and to analyze several related factors among ventilated patients at the Center of Anaesthesiology and Intensive Care, Bach Mai Hospital.Methods: A cross-sectional analytical study was conducted on 43 patients ventilated for ≥ 48 hours who received the ventilator-associated pneumonia prevention bundle from May 2024 to December 2024. Oral care practices were recorded through direct observation and medical records; oral care outcomes were assessed using the Beck oral assessment scale (BOAS). The associations between patient characteristics, care practices, and BOAS scores were analyzed.Results: 93.0% of patients received oral care ≥ 2 times/day; 97.7% used chlorhexidine-containing solutions; and 81.4% underwent oral suctioning prior to care. According to the BOAS, 74.4% achieved good results, 23.3% moderate, and 2.3% poor. Good oral care outcomes were significantly associated with age < 60, ventilation duration ≤ 7 days, intensive care unit stay ≤ 7 days, abdominal surgery, care frequency ≥ 2 times/day, and pre-care oral suctioning (p < 0.05).Conclusions: Oral care within the ventilator-associated pneumonia prevention bundle at the Center of Anaesthesiology and Intensive Care, Bach Mai Hospital was performed relatively well, with the majority of patients achieving good BOAS scores. Advanced age, prolonged ventilation, and extended intensive care unit stays were unfavorable factors; increasing care frequency and performing oral suctioning prior to care contributed to improved outcomes.
Keywords: Oral care, ventilator-associated pneumonia, VAP, BOAS, intensive care.